Dissolution rate of antigorite from a whole-rock experimental study of serpentinite dissolution from 2 < pH < 9 at 25 °C: Implications for carbon mitigation via enhanced serpentinite weathering. (October 2015) - Critelli, T.; Marini, L.; Schott, J.; Mavromatis, V.; Apollaro, C.; Rinder, T.; De Rosa, R.; Oelkers, E.H.
Highlights: Antigorite dissolution rates have been derived from whole-rock experiments at 2 < pH < 9 and 25 °C. Dissolution rates of antigorite above pH 7 are significantly lower than previously reported rates. The time required for serpentinite weathering is significantly higher than that estimated from literature data. Enhanced serpentinite weathering as a carbon capture/storage strategy may be less efficient than previously assumed. Abstract: Serpentinite rock dissolution experiments at 25 °C and 2 < pH < 9 were used to retrieve antigorite dissolution rates, as its high abundance and comparatively fast dissolution dominate element release from the rock. Retrieved antigorite dissolution rates at pH 2.02 and 3.06 are similar to previous literature data for serpentine minerals at corresponding pH. In contrast, retrieved rates at higher pH are considerably lower than corresponding literature data. Nonetheless, the retrieved rates at pH 5.76 and 7.28 are consistent with the linear log rate – pH relationship of Orlando et al. (2011), suggesting that rates follow a single 'acidic' mechanism to a pH of at least 7.3. The relatively low dissolution rates of serpentine minerals found in this study suggests that significantly more time is required for serpentine weathering than that estimated using the dissolution rates of these solids reported by Marini (2006) based on a review of literature data. As such, using enhanced serpentine weathering as a carbon capture/storage strategy may be less efficient than previously assumed.